Mindfulness-Based Cognitive Therapy for Treatment-Resistant Depression: A protocol for systematic review and meta-analysis. - Michele F Rodrigues; Larissa Junkes; Jose Appolinario; Antonio E Nardi (PLoS ONE)
Background Major Depressive Disorder (MDD) is a global health issue, and a significant portion of individuals with MDD experience Treatment-Resistant Depression (TRD), characterized by the lack of response to adequately trialed antidepressant medication and therapy. This systematic review aims to investigate the effectiveness of Mindfulness-Based Cognitive Therapy (MBCT) as an intervention for individuals with TRD. Materials and methods We will conduct a thorough search for publications of randomized clinical trials and quasi-experimental studies in MEDLINE, Embase, PsycINFO, Web of Science databases, and ClinicalTrials.gov. Furthermore, reference lists of included studies will be manually screened for additional relevant articles, with no restrictions on language or publication date. The search will be conducted from the inception of the databases until June 2024. Our PICO-guided research questions are: (1) In adults with Treatment-Resistant Depression, is MBCT more effective than standard care or other active treatments in reducing depressive symptoms? (2) In adults with Treatment-Resistant Depression, does MBCT demonstrate a comparable safety profile to standard care or other active treatments? The quality of the included studies will be assessed independently using the Cochrane Risk of Bias Tool (RoB 2). This study seeks to evaluate the effectiveness and tolerability of Mindfulness-Based Cognitive Therapy as an intervention for Treatment-Resistant Depression, and will employ the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology to appraise the confidence in the evidence. Prospero registration Prospero registration ID: CRD42023411978. Registered on April 07, 2023.